Differences in the Seed Germination of Leymus chinensis (Poaceae) Ecotypes Reveal Distinct Strategies for Coping With Salinity Stress: A Common Garden Experiment - Ma, Meng-Yao; Ma, Hong-Yuan; Wang, Lei; Qi, Wen-Wen; Li, Shao-Yang; Zhao, Dan-Dan (Frontiers in Ecology and Evolution, 2021)
Soil salinity is an important abiotic stress affecting various ecosystems worldwide such as grassland. Distinct ecotypes often evolve within species by natural selection to facilitate adaptation to different types of environmental stress. Leymus chinensis is a perennial rhizomatous grass that is widely distributed in the eastern Eurasian steppe; it has two main ecotypes, yellow-green (YG) and gray-green (GG), which differ in their strategy for coping with salinity stress. Few studies have examined the seed germination of the two ecotypes under salinity stress. In this study, the seed germination and seedling growth of two ecotypes of L. chinensis in response to different levels of salinity (NaCl) stress (0 (control), 20, 50, 100, and 200 mM) were examined. Ungerminated seeds were then placed under normal conditions to evaluate seedling growth following exposure to salt stress (i.e., re-germination). The germination percentage was significantly higher and the mean germination time significantly shorter in the GG ecotype than in the YG ecotype at all NaCl concentrations. As the salinity level increased, the radicle length of the two ecotypes decreased; however, GG had longer radicles and a higher number of radicles, even at 200 mM NaCl when no radicle protruding from the seed coat was detected in YG. The shoot length of GG was significantly longer than that of YG at all NaCl levels. After salinity stress was removed, the seed germination percentage increased as the original concentration of NaCl applied increased, but the total germination percentage did not significantly differ among NaCl concentrations. The total seed germination percentage of GG was approximately 80%, whereas that of the YG was approximately 20%. The seedlings length of re-germinated seeds for both GG and YG was similar. The thousand-grain weight of GG was significantly higher than that of YG. GG was more salt-tolerant than YG and might be better capable of surviving in harsher environments, suggesting that GG might be particularly useful for saline grassland restoration.